2015
DOI: 10.1177/2042098614560737
|View full text |Cite
|
Sign up to set email alerts
|

Targeting precision medicine toxicity: recent developments

Abstract: The European Society of Medical Oncology conference was held in Madrid, 26-30 September 2014. Its overriding theme was precision medicine in cancer care. A special symposium entitled 'Targeting precision medicine toxicity' looked specifically at the various toxicities caused by new targeted therapies. Cardiac toxicity Dr Lillian L. Siu (Princess Margaret Cancer Centre, Toronto, Canada) presented an overview of cardiac toxicities encountered with molecularly targeted agents. These include ventricular dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The mechanism of MAPKi‐mediated cardiotoxicities (heart failure, left ventricular dysfunction) is not well characterized, but preclinical data suggest that the MAPK pathway has a role in cardiac hypertrophy and cell survival . It has been understood since the early development of this drug class that cardiomyopathy is associated with MEKi, either alone or in combination with BRAFi .…”
Section: Current Management Strategies For Brafi‐ and Meki‐associatedmentioning
confidence: 99%
“…The mechanism of MAPKi‐mediated cardiotoxicities (heart failure, left ventricular dysfunction) is not well characterized, but preclinical data suggest that the MAPK pathway has a role in cardiac hypertrophy and cell survival . It has been understood since the early development of this drug class that cardiomyopathy is associated with MEKi, either alone or in combination with BRAFi .…”
Section: Current Management Strategies For Brafi‐ and Meki‐associatedmentioning
confidence: 99%
“…Cardiac‐related adverse events have been observed with both BRAFi and MEKi therapies , although they appear to be more strongly associated with MEKi. Initial studies with trametinib reported left ventricular ejection fraction (LVEF) dysfunction in 8% of patients compared with 5% of patients using combination therapy in the COMBI‐d trial in patients with BRAF V600‐mutant metastatic melanoma.…”
Section: Adverse Events and Managementmentioning
confidence: 99%
“…For instance, a review reported that only 2% of 296 patients who received 10 mg/kg of nivolumab exhibited hypotension. Similarly, only 7% of 135 melanoma patients who received 10 mg/kg of pembrolizumab showed a development of hypertension [ 160 ]. Cardiotoxic mechanisms are still to be elucidated, but mouse models suggest that heart dysfunction and dilation occur as an autoimmune response to cardiac troponin I in PD-1 deficient mice through chronic stimulation of Ca2+ influx [ 161 ].…”
Section: Reviewmentioning
confidence: 99%